Optimizations of expression and purification of recombinant HIV-1 CRF01_AE p24 protein in Escherichia coli for development of immunodiagnostic assay (Faculty of Medicine Universitas Indonesia, 2015)
Background: Conventional method for confirmation of HIV infection is Western blot. However, it has limitations because of contamination by human cellular antigen and genetic diversity among the HIV-1 subtypes that show indeterminate result and inaccuracy for the diagnosis of different strains. Most of Western blot developed are based on HIV-1 B subtype. In Indonesia HIV-1 CRF01_AE subtype is dominantly circulated. Therefore, we optimized the expression, purification of the recombinant HIV-1 CRF01_AE p24 protein for development of immunodiagnostic assay. Methods: Optimization of protein expression in Escherichia coli strain BL21CP was performed including induction time, isopropyl-1-thio-d-galactopyranoside (IPTG) and immidazole consentrations, and induction temperature. Purification of the recombinant p24 protein was used by using Ni-NTA (Qiagen) purification system in native condition. Results: Expression and purification of HIV-1 CRF01_AE p24 protein have been performed. Confirmation of the recombinant protein by Western blot showed the expression and purification of recombinant p24 protein has been optimized well and reactive with sera of patients with HIV-1 CRF01_AE subtype positive. Conclusion: The recombinant HIV-1 CRF01_AE p24 protein has been expressed and purified successfully, and it is potential to be used as antigen for immunodiagnostic assay.